Graded PVD Mo-Si interlayer between Si coating and Mo-Si-B alloys: Investigation of oxidation behaviour. (November 2021) - Anton, Ronja; Hüning, Steffen; Laska, Nadine; Weber, Matthias; Schellert, Steven; Gorr, Bronislava; Christ, Hans-Jürgen; Schulz, Uwe
Abstract: The insufficient oxidation resistance of Mo-Si-B alloys at high temperatures inevitably requires a protective coating. A dual layer system combining a graded Mo-Si interlayer with a Si oxidation protective top layer has been applied by magnetron sputtering on a Mo-9Si-8B alloy. The interlayer architecture was designed to maximize the adhesion between top layer and substrate by creating thermodynamic compatibility between alloy and Si. Isothermal oxidation tests at 800 and 1200 °C in air up to 300 h were performed focusing on chemical reactions between top layer, interlayer and substrate as well as the evolution of the thermally grown SiO2 . Graphical Abstract: ga1 Highlights: Using magnetron sputtering a graded Mo-Si interlayer and a Si top layer was developed on a Mo-9Si-8B alloy. The dual layer coating system suppressed pest oxidation at 800 °C and provided an excellent oxidation protection at 1200 °C due to the formation of a thermally grown oxide layer of SiO2 . At the coating – substrate interface a growing interdiffusion zone containing Mo-silicides analyzed by using TEM was developed providing excellent adhesion by overcoming the CTE mismatch between Si and Mo-9Si-8B alloy.